ANALISIS HUBUNGAN PENYAKIT PENYERTA DAN DURASI MENDERITA DENGAN KUALITAS HIDUP PENDERITA DIABETES - Alif, Nur Amalia; Metekohy, Feby Adolf; Wardani, Kartika Arum; Blongkod, Fitriani Rahmatismi (Ensiklopedia of Journal, 2026)
Abstract: Diabetes mellitus (DM) is a non-communicable disease characterized by elevated blood glucose levels above normal limits due to impaired insulin secretion, insulin action, or both. Epidemiologically, the 51–60 age group is the most common age group found to have diabetes mellitus. The purpose of this study was to analyze the relationship between comorbidities and duration of illness with the quality of life of people with diabetes. This study used a cross-sectional design. The study was conducted at the Pulomerak Community Health Center in April 2025. The study population consisted of all DM patients at the Pulomerak Community Health Center. The sample consisted of 150 respondents. The sampling technique used was simple random sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate analysis. The results showed a relationship between comorbidities (p value: 0.042) and duration of suffering (p value: 0.034) with the quality of life of people with diabetes. It is recommended that diabetes patients not only undergo examinations related to diabetes mellitus but also have their comorbidities checked and actively seek information related to diabetes mellitus management.Keywords: Diabetes, Duration of Suffering, Quality of Life.